Providing energy management of a fuel cell-battery-wind turbine-solar panel hybrid off grid smart home system - Arabul, Fatma Keskin; Arabul, Ahmet Yigit; Kumru, Celal Fadil; Boynuegri, Ali Rifat (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
It is important that smart home can use produced energy more effective and obtain optimum economy as well as provide ease of use. With use of fuel cell (FC) as main energy source in an off grid smart home that supplied by alternative energy sources (AES), more quality, economic and eco-friendly energy can be achieved. This off grid smart home system can use auxiliary energy sources with FC to supply instantaneous power and sustainable energy. Therefore, it is needed to develop energy management algorithms (EMA) for AES in smart home systems. These algorithms can be able to respond user's preferences and needs and also enable to benefit optimally from AES. In line with these requirements in this study, an EMA for a smart home, which is equipped with FC, battery, solar panel and wind turbine is presented. A fuzzy logic controller is designed for EMA. The proposed system is tested in MATLAB/Simulink and obtained results of the simulation are analyzed and discussed. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuel cell hybrid power source; Energy management; Smart home; Load demand management; PORTABLE APPLICATIONS; POWER MANAGEMENT; HYDROGEN; STRATEGIES; EFFICIENCY; ALGORITHM; Chemistry; Electrochemistry; Energy & Fuels